2020
DOI: 10.32479/ijefi.9354
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Economic Cycle With a Structural Equation Model: Evidence From Thailand

Abstract: The study proposes a partial least squares structural equation modeling (PLS-SEM) evaluating the relationship among composite leading indices (CLIs) to forecast the economic cycle (EC) instead of using only individual CLI. The model of quarterly data in Thailand during 2013-2018 includes five constructs representing economic sectors that have the potential to be CLIs of EC. Those are two short-term CLIs including Short-leading economic index (SLEI) and International transmission (Trade channel) (ITT). SLEI com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The government should take appropriate, timely and effective steps for the revival of the economy in such situation of crisis (Lahoti et al, 2020). The Financial cycle includes Housing price index, Household debt to GDP, and Household debt (Pumjaroen et al, 2020). The investors should not follow sentiment indicators blindly and found that aggressive stocks have high volatility and gain investor attention during optimistic and pessimistic market conditions (Yelamanchili, 2019).…”
Section: Middle Class Strategies To Generate Novel Sources Of Income Due To Covid-19 Disruption Of Their Mhi and Budgetmentioning
confidence: 99%
“…The government should take appropriate, timely and effective steps for the revival of the economy in such situation of crisis (Lahoti et al, 2020). The Financial cycle includes Housing price index, Household debt to GDP, and Household debt (Pumjaroen et al, 2020). The investors should not follow sentiment indicators blindly and found that aggressive stocks have high volatility and gain investor attention during optimistic and pessimistic market conditions (Yelamanchili, 2019).…”
Section: Middle Class Strategies To Generate Novel Sources Of Income Due To Covid-19 Disruption Of Their Mhi and Budgetmentioning
confidence: 99%